THE DETERMINANTS OF VALUE PARADIGM OF M. CASTELLS’ NETWORK SOCIETY IN THE CONTEXT OF ITS MULTIDIMENSIONAL ARCHITECTURE - Кузнецов, А. Ю.; Пустовіт, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The network economy, labor market, transformation of sociability and communication sphere as social contexts of network society have been considered in this paper